Analisis Hak-Hak Khusus Narapidana Perempuan Yang Merupakan Tanggung Jawab Negara Dilembaga Pemasyarakatan - Ahmad Agung Raharjo; Mitro Subroto (Universitas Widya Gama Malang, 2022)
Inmate is a term for someone who is serving a criminal period of lost independence in the correctional institution, this is the impact of his actions or behavior that legally violates the law and norms of life in the community. Even though they are serving time in prison, their natural rights are still attached to themselves and it should be underlined, that the state only takes their right to independence, not their right to life or anything else, their fundamental rights are still attached to the body. especially when it comes to female prisoners who are classified as vulnerable groups, female prisoners are a vulnerable group because they require special treatment for their needs even though basically their rights are the same as inmates in general, namely male prisoners, but related to gender roles and reproductive functions, they are certainly different and there is a need for special treatment when they are pregnant, giving birth, breastfeeding, nursing or menstruating. The purpose of this research is to examine how the implementation of the fulfillment of the special rights of vulnerable groups of female prisoners in the Penitentiary. The research method uses Normative Legal Techniques where the source of research data comes from library materials, regulations and various journal literature to conclude the results of qualitative descriptive analysis related to the fulfillment of the special rights of female prisoners in Correctional Institutions, especially Women Correctional Institutions in several Correctional Technical Implementing Units in Indonesia.